Increased β2-adrenoceptor phosphorylation in airway smooth muscle in severe asthma: possible role of mast cell-derived growth factors. (30th September 2018) - Chachi, L; Alzahrani, A; Koziol-White, C; Biddle, M; Bagadood, R; Panettieri, R A; Bradding, P; Amrani, Y
Summary: The purpose of this study was to investigate whether growth factors produced by activated human lung mast cells (HLMCs) impair β2 -adrenoceptor (β2 -AR) function in human airway smooth muscle (ASM) cells. Protein array analysis confirmed the presence of various growth factors, including transforming growth factor (TGF)-β1, in the supernatants of high-affinity IgE receptor (FcεRI)-activated HLMCs which, when applied to ASM cells, impaired albuterol-induced cyclic adenosine monophosphate (cAMP) production, an effect that was prevented following neutralization of TGF-β1. This blunted β2 -AR response was reproduced by treating ASM cells with TGF-β1 or fibroblast growth factor (FGF)-2, which induced β2 -AR phosphorylation at tyrosine residues Tyr 141 and Tyr 350, and significantly reduced the maximal bronchorelaxant responses to isoproterenol in human precision cut lung slices (PCLS). Finally, ASM cells isolated from severe asthmatics displayed constitutive elevated β2 -AR phosphorylation at both Tyr 141 and Tyr 350 and a reduced relaxant response to albuterol. This study shows for the first time that abnormal β2 -AR phosphorylation/function in ASM cells that is induced rapidly by HLMC-derived growth factors, is present constitutively in cells from severe asthmatics. Graphical Abstract: